Humeral head hemiarthroplasty for patients with avascular necrosis following a solid organ transplant: A report of three shoulders - Amogh I. Iyer; Andrew J. Stevens; Akshar V. Patel; Gregory Cvetanovich; Julie Y. Bishop; Ryan C. Rauck (Journal of Orthopaedic Reports, 2024)
Background: Avascular necrosis (AVN) is a common occurrence following solid organ transplant (SOT) due to chronic steroid use. We report on three shoulders of humeral head hemiarthroplasty (HHA) in the setting of AVN after SOT. This topic is an important issue to study as there is limited literature on AVN requiring shoulder arthroplasty following SOT. As the prevalence of SOT continues to rise, it is important to study this population before making guidelines in the future. Case presentations: In one shoulder, a 51-year-old male presented with AVN of the left shoulder three years after undergoing a lung transplant and taking 5mg oral prednisone daily. In the second and third shoulder, a 61-year-old female presented with AVN of bilateral shoulders two years after undergoing a kidney transplant and taking 7.5mg oral prednisone daily. All three shoulders went on to have HHA with improved outcomes after surgery at a mean follow-up of 4.6 years. Conclusion: Shoulder arthroplasty is safe and effective for patients with avascular necrosis after a SOT.